2009
DOI: 10.1111/j.1743-6109.2009.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

A Report from a Single Institute’s 14-Year Experience in Treatment of Male-to-Female Transsexuals

Abstract: Introduction Gender identity disorder or transsexualism is a complex clinical condition, and prevailing social context strongly impacts the form of its manifestations. Sex reassignment surgery (SRS) is the crucial step of a long and complex therapeutic process starting with preliminary psychiatric evaluation and culminating in definitive gender identity conversion. Aim The aim of our study is to arrive at a clinical and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 27 publications
1
79
0
Order By: Relevance
“…Perspectives from the trans community demonstrate a similar concern over lack of information on long-term outcomes and potential complications of gender transitioning treatments [13]. The literature on patient satisfaction after surgical transitioning is not extensive, but suggests that patient regret is relatively minimal, with a prevalence ranging from 2-6 % depending on the procedure [33-35]. Clinical guidelines were seen as a way to address knowledge deficits in gender transitioning treatments and preventative screening, but were not without criticism.…”
Section: Discussionmentioning
confidence: 99%
“…Perspectives from the trans community demonstrate a similar concern over lack of information on long-term outcomes and potential complications of gender transitioning treatments [13]. The literature on patient satisfaction after surgical transitioning is not extensive, but suggests that patient regret is relatively minimal, with a prevalence ranging from 2-6 % depending on the procedure [33-35]. Clinical guidelines were seen as a way to address knowledge deficits in gender transitioning treatments and preventative screening, but were not without criticism.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Unfortunately, the applicability of these findings in guiding policy and future research is impacted by wide variation in the findings of suicidality rates. 4,5 For example, Xavier et al 6 report an attempt rate of 25% and an ideation rate of 65%, while Imbimbo et al 7 record rates of 3% and 50%, respectively. The current meta-synthesis attempts to address these discrepancies by measuring the overall variation across and averaging the suicidality rates within these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Imbimbo et al [16] reported on 163 male-tofemale patients operated on over a 17-year period. 89% engaged in postsurgical sexual activity with 75% having a more satisfactory sex life after surgery.…”
Section: Key Pointsmentioning
confidence: 99%